Evidence of housing instability identified by addresses, clinical notes, and diagnostic codes in a real-world population with substance use disorders - Daniel R. Harris; Nicholas Anthony; Dana Quesinberry; Chris Delcher (Journal of Clinical and Translational Science, 2023)
Abstract